Perspectives on Language and Language Development Essays in honor of Ruth A. Berman - Ravid, Dorit Diskin; Bat-Zeev Shyldkrot, Hava (Springer US : Imprint: Springer, 2005)
Perspectives on Language and Language Development brings together new perspectives on language, discourse and language development in 31 chapters by leading scholars from several countries with diverging backgrounds and disciplines. It is a comprehensive overview of language as a rich, multifaceted system, inspired by the lifework of Ruth A. Berman. Edited by Dorit Ravid and Hava Bat-Zeev Shyldkrot, both from Tel Aviv University, Israel, the book offers state-of-the-art portrayals of linguistic and psycholinguistic phenomena with new insights on the interrelations of language structure, discourse theory, and the development of language and literacy. The volume presents innovative investigations on the interface of language and narrative in a broad range of languages, with a section devoted to linguistic studies of Modern Hebrew. It traces the development of language and literacy from early childhood through adolescence to maturity in spoken and written contexts, and in monolingual as well as multilingual perspectives. Linguists, psycholinguists, discourse scholars, cognitive psychologists, language teachers, education experts, and clinicians working in the field of language and discourse will find this book extremely useful both as a textbook and as a source of information.